Islam in modern Thailand : faith, philanthropy and politics - Brown, Rajeswary Ampalavanar, 1943- (London : Routledge, 2014)
'This book addresses the complexity of Islam in Thailand, by focusing on Islamic charities and institutions affiliated to the mosque. By extrapolating through Islam and the waqf (Islamic charity) in different regions of Thailand the diversity in races and institutions, it demonstrates the regional contrast within Thai Islam. The book also underlines the importance of internal histories of these separate spaces, and the processes by which institutions and ideologies become entrenched. It goes on to look at the socio economic transformation that is taking place within the context of trading networks through Islamic institutions and civil networks linked to mosques, madrasas and regional power brokers'--
Includes bibliographical references and index.
Keywords: Islam -- Thailand; Waqf -- Thailand